2017
DOI: 10.3389/fnagi.2017.00106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microbiota-Gut-Brain Axis on Diabetic Cognition Impairment

Abstract: Progressive cognitive dysfunction is a central characteristic of diabetic encephalopathy (DE). With an aging population, the incidence of DE is rising and it has become a major threat that seriously affects public health. Studies within this decade have indicated the important role of risk factors such as oxidative stress and inflammation on the development of cognitive impairment. With the recognition of the two-way communication between gut and brain, recent investigation suggests that “microbiota-gut-brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 214 publications
0
39
0
1
Order By: Relevance
“…However, the gut–brain axis also mediates the neuroinflammatory response after a vascular injury, such as ischemic stroke 124. Additionally, diabetes mellitus and obesity, which are among the main conditions predisposing to vascular dementia, are both associated with gut microbiota alterations and/or dysbiosis 125,126. Thus, the gut microbiota may also be involved in vascular cognitive impairment, mainly through modulation of local neural and systemic inflammation and insulin sensitivity 127…”
Section: Discussionmentioning
confidence: 99%
“…However, the gut–brain axis also mediates the neuroinflammatory response after a vascular injury, such as ischemic stroke 124. Additionally, diabetes mellitus and obesity, which are among the main conditions predisposing to vascular dementia, are both associated with gut microbiota alterations and/or dysbiosis 125,126. Thus, the gut microbiota may also be involved in vascular cognitive impairment, mainly through modulation of local neural and systemic inflammation and insulin sensitivity 127…”
Section: Discussionmentioning
confidence: 99%
“…In one recently published study the authors found also lower levels of ghrelin in T2DM patients with MCI compared to those with healthy cognition [9]. Other researchers found that ghrelin is an important predictor of executive function impairment in patients with type 2 diabetes [10]. Both studies mention above Ghrelin Levels in Elderly, Diabetic Patients with Mild Cognitive Impairment were performed in much younger population than our study, which the first examine serum ghrelin levels in elderly subjects.…”
Section: Discussionmentioning
confidence: 64%
“…The executive function could be a sensitive indication of diabetic cognitive decline among diabetes population. The author proposed that serum ghrelin level might be a biomarker of executive function in patients with type 2 diabetes mellitus [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations